1994
DOI: 10.1007/bf01088426
|View full text |Cite
|
Sign up to set email alerts
|

Thiocyanate levels of mainly dietary origin in serum and urine from a human population sample in Port Harcourt, Nigeria

Abstract: Thiocyanate levels were determined in serum and urine samples obtained from a human population sample of healthy non-smoking volunteers (aged between 14 and 30 years) of both sexes known to eat gari-based meals at least once a day. The samples were collected before and 3-4 hours after a gari- or rice-based meal. The values obtained before the test meals showed a wide variation, ranging between 39.20 +/- 1.95 to 160.95 +/- 8.06 mumol/l of serum, and 81.92 +/- 9.78 to 294.01 +/- 14.70 mumol/l of urine. For each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…Urinary excretion may not reflect circulating levels because in part thiocyanate is formed in vivo from cyanide (10), present in certain foods (11), and formed during protein metabolism (10). In smokers, cigarette smoke is an important source of HCN (12).…”
Section: Introductionmentioning
confidence: 99%
“…Urinary excretion may not reflect circulating levels because in part thiocyanate is formed in vivo from cyanide (10), present in certain foods (11), and formed during protein metabolism (10). In smokers, cigarette smoke is an important source of HCN (12).…”
Section: Introductionmentioning
confidence: 99%
“…These observations might increase the risk of a cassava-eating population to the carcinogenic activities of nitrates and nitrite in vegetables that they consume. A previous report (Eminedoki et al 1994) has demonstrated that daily consumption of a cassavabased diet by human subjects increases the level of thiocyanate in their serum and urine. Therefore, the control of nitrate and nitrite intake may be important in Delta State, Nigeria, where plasma thiocyanate content is generally high because of the consumption of cassava-based diets, and especially now that the nitrate levels in V. amygdalina (bitter leaf), and Telfaria occidentalis (pumpkin) grown in the industrialised regions of the state are within the reference levels reported to be associated with an increased incidence of gastric cancer (Armijo et al 1981;Dutt et al 1987).…”
Section: Discussionmentioning
confidence: 95%
“…In order to study optimal derivatization conditions, the reaction was performed for various amounts of D-cysteine and sodium hypochlorite (0.25, 0.5, 1.0, 1.25, 1.5, and 1.75 mM) and reaction times (2,5,8,10,20,30, and 40 min) at room temperature in water. Derivatization efficiencies were calculated at various pH levels (3.0, 4.0, 4.5, 5.0, 5.5, 6.0, 7.0, 8.0, and 9.0) at room temperature.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%